2010
DOI: 10.1177/0265407509360898
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in adolescence: A move to the level of emotion regulation

Abstract: The early adolescent's state of mind in the Adult Attachment Interview (AAI) is more closely linked to social interactions with peers, who are unlikely to serve as attachment figures, than it is to (i) qualities of the adolescent's interactions with parents, (ii) the AAI of the adolescent's mother, or (iii) the adolescent's prior Strange Situation behavior. This unexpected finding suggests the value of reconceptualizing AAI autonomy/security as a marker of the adolescent's capacity for emotion regulation in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 24 publications
6
118
0
2
Order By: Relevance
“…The overall pattern of results across these studies support that attachment anxiety and avoidance are associated with heightened autonomic reactivity. Such findings are consistent with the notion that attachment insecurity is associated with deficits in emotion regulation (Allen & Miga, 2010;Mikulincer et al, 2003). Furthermore, attachment systems appear to be implicated in individual differences of autonomic capacities for effective emotion regulation.…”
Section: Relationship Between Hrv and Factors Of Psychological Resilisupporting
confidence: 90%
“…The overall pattern of results across these studies support that attachment anxiety and avoidance are associated with heightened autonomic reactivity. Such findings are consistent with the notion that attachment insecurity is associated with deficits in emotion regulation (Allen & Miga, 2010;Mikulincer et al, 2003). Furthermore, attachment systems appear to be implicated in individual differences of autonomic capacities for effective emotion regulation.…”
Section: Relationship Between Hrv and Factors Of Psychological Resilisupporting
confidence: 90%
“…It extends the literature on attachment and mindfulness by identifying mediating variables associated with maladaptive, but potentially modifiable, cognitive-emotional patterns. Like other attachment investigators (Allen & Miga, 2010), we have advocated for a "move to the level of emotion regulation" in attachment research, a move that, in our opinion, will open the door to more effective clinical interventions for healing attachment-related wounds. Mindfulness may play an important role in this process by shifting peoples' experiences of themselves, others, and their environments in ways that foster personal and interpersonal well-being.…”
Section: Discussionmentioning
confidence: 97%
“…Close friends become significant attachment figures who can represent a secure base for the youth as they manage the emotional stress and challenges of adolescence (Meurling, Ray, & LoBello, 1999). Research has shown that peer relationship qualities are more strongly associated with adolescent attachment security than are parental relationship qualities, even during early and mid-adolescence (Allen & Miga, 2010). Yet the quality of an adolescent's friends can vary, either serving as a positive source of emotional support and caring or contributing to fears of rejection and psychological insecurity.…”
Section: Introductionmentioning
confidence: 99%